2017
DOI: 10.1002/qua.25571
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐density delocalization in many‐electron atoms confined by penetrable walls: A Hartree–Fock study

Abstract: The electronic structure of several many-electron atoms, confined within a penetrable spherical box, was studied using the Hartree-Fock (HF) method, coupling the Roothaan's approach with a new basis set to solve the corresponding one-electron equations. The resulting HF wave-function was employed to evaluate the Shannon entropy, S q , in configuration space. Confinements imposed by impenetrable walls induce decrements on S q when the confinement radius, R c , is reduced and the electron-density is localized. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 54 publications
4
53
0
2
Order By: Relevance
“…Interestingly, our ionization pressures agree with the prediction of Hoffmann et al that no element of the second period ionizes for pressures below than 500 GPa but lithium, which does below 80 GPa. We also estimate the ionization pressure of Li from recent HF calculations with hard walls done by Rodriguez et al Despite the restricted data, we found that the ionization pressure (30 GPa) agrees very well with our HF value (27 GPa). This nice agreement strongly supports our scheme to translate values of ω into pressure.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Interestingly, our ionization pressures agree with the prediction of Hoffmann et al that no element of the second period ionizes for pressures below than 500 GPa but lithium, which does below 80 GPa. We also estimate the ionization pressure of Li from recent HF calculations with hard walls done by Rodriguez et al Despite the restricted data, we found that the ionization pressure (30 GPa) agrees very well with our HF value (27 GPa). This nice agreement strongly supports our scheme to translate values of ω into pressure.…”
Section: Resultssupporting
confidence: 77%
“…Other kind of works have been done by Garza et al They also began with the study of confined atoms in a hard spherical cavity. However, they interpreted the results in terms of pressure by using the thermodynamic relation P=EV and they also derived an equation to calculate the Gibbs free energy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rodriguez-Bautista et al showed that the Shannon entropy in the configuration space, [19] S ρ = drρ(r) ln ρ(r) (23) gave information of the delocalization (or localization) of an atomic system when spherical cavities trapped atoms with infinite or finite potential. In specific, these authors showed that this quantity decreased when hard walls confined the system.…”
Section: Methodsologymentioning
confidence: 99%
“…[15][16][17][18][19] For this confinement, some atoms delocalize their electron density when the barrier height, associated to a constant potential, and R c are small. [15][16][17][18][19] For this confinement, some atoms delocalize their electron density when the barrier height, associated to a constant potential, and R c are small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation